Building Nanoscale Molecular Wires Exploiting Electrocatalytic Interactions - Zagal-Moya, J; Zagal-Moya, J; Caroli-Rezende, M; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Ponce-Hormazabal, I; Onate, R (Elsevier Ltd, 2015)
Herein, we present a novel method to design nanoscale molecular wires by exploiting well-established electrocatalytic molecular platforms based on metallophthalocyanine blocks. Metallophthalocyanines exhibit high catalytic activity for a wide variety of electrochemical reactions of practical interests. To this aim, metallophthalocyanine molecules can be attached to an electrode surface via a conjugated mercaptopyridine axial ligand that provides (i) stable chemical binding to the metal surface through the thiol-anchoring group, and (ii) a good electrical communication between the metallophthalocyanine ring and the electrode surface. Our previous work demonstrates that long mercaptopyridinium blocks act as excellent linkers in such electrocatalytic platform, resulting in an optimal electrocatalytic activity of the metallophthalocyanine unit. Here we profit from this optimized electrocatalytic molecular platform to design new molecular wires that connect a metal nanoscale junction in a highly efficient and tunable way. To this aim, we use an STM break-junction approach to control the formation of a nanometric gap between two Au electrodes, both functionalized with mercaptopyridinium (bottom) and mercaptopyridine (top). When metallophthalocyanine is introduced into the functionalized metal nanojunction, stable molecular connections between the two electrodes are formed through axial coordination to the top and bottom pyridine moieties. We show that the highest conductance of the resulting nanoscale molecular wire corresponds to an Fe-phthalocyanine as compare to a Cu-phthalocyanine, which follows the electrocatalytic trend for such molecular systems. These results not only demonstrate a new strategy to design new families of highly conductive and tunable nanoscale molecular wires, but it also brings a new nanoscale electrical platform to help understanding some fundamental mechanistic aspects of molecular electrocatalysis. © 2015 Elsevier Ltd. All rights reserved.